PENDIDIKAN AGAMA ISLAM INDONESIA SEBAGAI SUBSISTEM PENDIDIKAN NASIONAL - Masthu Mastuhu (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2006)
It is necessary for Islamic educational institutions to have the power of changing themselves to be able to take part in determining the ideal and success of national education. Precisely, today, Islamic educational system is perceived weak and powerless in the dynamic of social changes have been occurring in the society. Even, this situation, it is frequently assumed as the burden of national education. Why can it be so? Aren't Islamic educational providers are also referring to the only one Law, that is, Law Number 20 year 2003 regarding National Educational System? What is wrong with Islamic education ? How is the quality of human resources of these providers? This article tries to answer those questions. This article also deals with analogue of Islamic Education as a subsystem of national education with family system in Islam. Family is a system. Child is a subsystem of the family. The more the child is matured and independent the better his/her family is.